2018
DOI: 10.1098/rsos.180482
|View full text |Cite
|
Sign up to set email alerts
|

A Late Cretaceous mammal from Brazil and the first radioisotopic age for the Bauru Group

Abstract: In the last three decades, records of tribosphenidan mammals from India, continental Africa, Madagascar and South America have challenged the notion of a strictly Laurasian distribution of the group during the Cretaceous. Here, we describe a lower premolar from the Late Cretaceous Adamantina Formation, São Paulo State, Brazil. It differs from all known fossil mammals, except for a putative eutherian from the same geologic unity and Deccanolestes hislopi, from the Maastrichtian of India. The incompleteness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 61 publications
2
35
0
Order By: Relevance
“…The fossil content of the Bauru Basin is mainly concentrated in the Bauru Group, which records a plethora of vertebrates, including dinosaurs, crocodilians, turtles, lizards, anurans, birds, and mammals 28–30 . As a whole, the fauna of the Bauru Group indicates a Coniacian to Maastrichtian age 27 , as corroborated by a recent radioisotopic dating 31 . Fossils are much rarer in the Caiuá Group, hampering the determination of its biostratigraphic correlations.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…The fossil content of the Bauru Basin is mainly concentrated in the Bauru Group, which records a plethora of vertebrates, including dinosaurs, crocodilians, turtles, lizards, anurans, birds, and mammals 28–30 . As a whole, the fauna of the Bauru Group indicates a Coniacian to Maastrichtian age 27 , as corroborated by a recent radioisotopic dating 31 . Fossils are much rarer in the Caiuá Group, hampering the determination of its biostratigraphic correlations.…”
Section: Introductionsupporting
confidence: 53%
“…Nonetheless, the scarce record of pterosaurs in general casts doubts upon their utility for such correlations. On the other hand, a younger (Late Cretaceous) age can be suggested based on its inferred depositional synchronicity 21 with rocks of the recently dated (as Coniacian to Campanian) Adamantina Formation 31 . According to some stratigraphic schemes, the Caiuá Group is composed of three coeval units: the Rio Paraná, Goio Erê, and Santo Anastácio formations.…”
Section: Geological Settingsmentioning
confidence: 99%
“…There are no integrative absolute date studies for the Adamantina Formation to specify the age correlation among the different fossiliferous localities found in the Bauru Group. Recently, the first high-precision U-Pb geochronology study has shown a post-Turonian maximal age ( ≤ 87.8 Ma) for the type stratum of Brasilestes stardusti ( Castro et al., 2018 ), which is overlain by the dinosaur-bearing Marília Formation; this age thus constrains the maximum age of the Adamantina Formation at the Boipeba site. The minimum age is not well constrained, but presence of non-avian dinosaurs in higher beds implies an age pre-dating the Cretaceous-Paleogene (K/Pg) boundary (66 Ma) ( Batezelli, 2017 ; Menegazzo et al., 2016 ).…”
Section: Resultsmentioning
confidence: 97%
“…As a consequence, following the reasoning that Uberaba and Adamantina formations can be correlated, at least part of the Adamantina Formation can be considered Campanian. A recent study ( Castro et al, 2018 ) provides high-precision U-Pb post-Turonian maximal age for an outcrop of the Adamantina Formation located in western São Paulo state, suggesting a late Coniacian–late Maastrichtian temporal constraint. However, the absolute age of the FTA’s outcrops is unknown and we consider them as belong to the upper part of the Late Cretaceous.…”
Section: Introductionmentioning
confidence: 99%